2013
DOI: 10.1055/s-0033-1351659
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Outcomes of Very Low Birth Weight Preterm Infants Treated With Poractant Alfa versus Beractant for Respiratory Distress Syndrome

Abstract: Our findings suggest that poractant alfa and beractant are similar in terms of neurodevelopmental outcomes when used for the treatment of RDS in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Fourteen studies had mid-term to long-term outcomes (>72 h) [ 19 , 20 , 22 33 ], and 1 study had short-term outcomes (≤72 h) [ 21 ]. The criterion for gestational age was <37 or ≤37 wGA in five studies [ 22 , 24 , 25 , 29 , 32 ], <35 wGA in two studies [ 19 , 26 ], ≤32 wGA in three studies [ 20 , 27 , 28 ], <30 wGA in one study [ 31 ], 26–36 wGA in one study [ 33 ], and 24 to <30 wGA in one study [ 21 ]. Two studies simply stated that patients had to be preterm, without defining a specific gestational age [ 23 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen studies had mid-term to long-term outcomes (>72 h) [ 19 , 20 , 22 33 ], and 1 study had short-term outcomes (≤72 h) [ 21 ]. The criterion for gestational age was <37 or ≤37 wGA in five studies [ 22 , 24 , 25 , 29 , 32 ], <35 wGA in two studies [ 19 , 26 ], ≤32 wGA in three studies [ 20 , 27 , 28 ], <30 wGA in one study [ 31 ], 26–36 wGA in one study [ 33 ], and 24 to <30 wGA in one study [ 21 ]. Two studies simply stated that patients had to be preterm, without defining a specific gestational age [ 23 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies included between 30 and 293 patients. Nine studies included data about doses that were administered according to the US product label (i.e., beractant 100 mg/kg; poractant alfa 200 mg/kg for the first dose, and 100 mg/kg for subsequent doses) [ 19 , 20 , 22 , 23 , 25 , 27 , 29 , 31 , 33 ]. Six studies specifically compared beractant 100 mg/kg with poractant alfa 100 mg/kg [ 19 , 24 , 26 , 28 , 30 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared to our previous metaanalysis on respiratory endpoints, there was one more study reporting on the extra-pulmonary outcomes [45]. This study did not report the exact dose of surfactant [45]. Moreover, Fujii et al reported hemodynamically significant PDA in one paper and other extra-pulmonary outcomes in a second manuscript [30,31].…”
Section: Additional Analysesmentioning
confidence: 86%
“…Additionally, we also searched PubMed, using key words and/or MeSH terms as described in the Additional file 1, looking for animal or human translational investigations on these mechanisms. Fig.1 illustrates the project flow-chart: we included 17 studies in the systematic review [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] and we excluded two papers from the meta-analysis, as they investigated two non-internationally marketed porcine surfactants [43,44]. Compared to our previous metaanalysis on respiratory endpoints, there was one more study reporting on the extra-pulmonary outcomes [45].…”
Section: Additional Analysesmentioning
confidence: 99%
See 1 more Smart Citation